Tinjauan Yuridis Keadilan Restoratif dalam KUHP Baru sebagai Instrumen Dekongesti terhadap Overcrowding Lembaga Pemasyarakatan di Indonesia - Nazwa Queena Amelia Fanany (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to determine the regulation of restorative justice in Law Number 1 of 2023 concerning the Criminal Code, as well as the role of restorative justice in Law Number 1 of 2023 concerning the Criminal Code as an instrument of decongestion (reducing overcrowding) in Correctional Institutions. The type of research used is normative juridical with a statutory and conceptual approach. The results of the study indicate that Law Number 1 of 2023 concerning the Criminal Code does not explicitly regulate restorative justice as a mechanism for resolving criminal cases, but its values ​​have been internalized through the objectives of punishment, sentencing guidelines, judicial pardon, and alternative punishment regulations, such as supervision and community service. These regulations reflect a shift in the paradigm of punishment from a retribution-oriented approach to recovery and social reintegration. Furthermore, the restorative justice values ​​in the New Criminal Code serve as an instrument for decongestion in correctional institutions by strengthening alternative punishments, potentially reducing the use of imprisonment and curbing overcrowding. Although their effectiveness depends on implementation by law enforcement officials.